Pubertal spurt and body build of schoolgirls from Merida, Yucatan, Mexico - Zielińska, Anna (Studia Ecologiae et Bioethicae, 2003)
The patterns of physical growth (stature, BMI, subscapular and arm fat-fold thickness, upper and lower extremity length, chest circumference, arm, and hip breadth, and age at menarche) were studied in 857 of Maya and Mestizo girls and 1314 of Creole girls aged 6-18 years. Data were collected between 1998-2001 in primary, secondary, and high schools of Merida, Capital City of the Yucatan State, Mexico. The ethnicity of girls was defined using their two surnames (from the father and mother side). The results show that Creoles are taller, have more abundant fat tissue, and greater BMI, especially at the age of 11 years, which means that they are better prepared to start pubertal spurt. Maya girls have relatively longer upper extremities to lower ones, greater biacromial breadth, and chest circumference to stature than Creoles, which shows their more stocky body build. The adolescent (pubertal) spurt in height starts earlier in Creoles (9-10 years) and its rate is greater (max. = 7.48 cm/ year) than in Maya and Mestizos girls (10-11 years; max. = 6.25 cm/year). In Mayas and Mestizos, there is only a slight difference between the rate of changes before and during the pubertal spurt. There are no significant differences in age at menarche between girls from both ethnic groups (11.96 in Mayas and Mestizos and 12.04 in Creoles), but there are statistically significant differences between age at menarche of studied girls and their mothers (12.4 for both groups) in each ethnic group. There is evidence that the onset of pubertal spurt in height and its rate may depend on ethnicity. Creoles may lead to more “westernized” style of life than the Maya and Mestizos girls.